PENGARUH FUNDAMENTAL SAHAM DAN MAKRO EKONOMI TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMEN PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Darmawan, Dahlia; Notoatmojo, M. Iqbal (Jurnal Akuntansi dan Bisnis, 2023)
This study aims to analyse the effect of Return On Equity, Debt to Equity Ratio, Earning Per Share and Inflation on stock prices using the panel data regression analysis method with the eviews application. This study uses purposive sampling technique in sampling. The samples in this study consist of 14 companies from a total population of 117 manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange for the period 2018-2022. The results showed that partially Earning Per Share has a significant effect on stock prices, Debt to Equity Ratio has a negative and significant effect on stock prices, while Return On Equity and inflation have no effect on stock prices. While simultaneously Return On Equity, Debt to Equity Ratio, Earning Per Share and inflation affect stock prices.. Keywords: Return On Equity, Debt to Equity Ratio, Earning Per Share, Inflation, Stock Prices.